THE BIOPSYCHOSOCIAL NATURE OF PAIN: FROM NOCICEPTION TO AFFECTIVE DISORDERS - Koliada, Nataliia; Deineka, Kyrylo (Personality and environmental issues, 2026)
Pain is considered a complex phenomenon that cannot be described solely as tissue damage. According to modern biopsychosocial concepts, the sensation of pain is formed from the linear coding of nociceptive signals in the peripheral sensory system to the integration of information in the spinal nervous system and brain, with modulation by cognitive mechanisms. The aim of this work is to comprehensively analyse and systematise existing scientific data on the processes of forming subjective pain perception from lower to higher levels.The article discusses the types of peripheral neurons, in particular nociceptive A-delta and C fibre types of sensory neurons, as well as the mechanisms of information processing in the spinal cord according to the theories of population coding, combination coding and the mechanisms of lateral inhibition, central sensitisation and spatial summation. Regarding the integration of pain in the brain, the Neuromatrix theory is considered, which postulates the distribution of functions throughout the brain, rather than the presence of irreplaceable regions responsible for pain perception.Particular attention is paid to the bidirectional interaction between the spinal nervous system and the brain. The article discusses the most current theory of descending pain modulation, called Predictive Coding Theory. It describes the role of prediction errors, which are processed within brain structures such as the anterior cingulate cortex and insular cortex, in the formation of subjective pain perception. Additionally, the main psychological modulators of this process are attention, expectation, interpretation, anxiety, stress, and depression. The paper describes the results of studies on the neurobiological and psychological mechanisms of mediation in the formation of subjective pain perception and the physiological response of the nervous system.A separate consideration is given to the phenomenon of chronic pain under the influence of prolonged stress, as well as its common neurological processes and high comorbidity with depression.